Unsur Visual Kemasan Granola Creations - Desintha, Siti; Ayu, Intan Kusuma; Octamediana, Haliza (Universitas Komputer Indonesia, 2020)
Granola Creations is a food product originating from Bali, Indonesia and produced by Hundred Seeds. The products are health food made from a mixture of cereals, oats, nuts, sugar and baked dried fruits. Granola Creations has the appearance of a packaging with a dominant brown color, and images of the contents of the product. Basically, packaging as the main image provider of a product to the target audience. The results of the research show that Granola Creations packaging uses text, layout, texture and certain colors that are suitable for conveying information, the identity, personality and image of the product. The study was conducted to determine whether the visual elements in the packaging display used are in accordance with the image of the Granola Creations product. This research uses descriptive analysis method with elemental approach, Visual Communication Design principles and analysis based on packaging material. The results showed that Granola Creations successfully displayed communicative packaging through visual appearance and physical form of packaging in one food packaging design